Dampak Artificial Intelligence (AI) Pada Efisiensi Operasional Bank: Studi Literatur - M. Guffar Harahap; Haidir; Muhamad Hizbulllah (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2025)
The rapid advancement of Artificial Intelligence (AI) has transformed the operational landscape of the banking sector, enabling more efficient and accurate processes. This study aims to analyze the impact of AI on improving operational efficiency in Indonesian banking institutions. A literature review approach was used by examining national and international research related to AI applications in banking operations. The findings show that technologies such as chatbots, machine learning, and Robotic Process Automation (RPA) enhance employee productivity, strengthen internal audit functions, and lower BOPO ratios. AI also contributes to cost reduction and real-time risk control. However, challenges remain in terms of investment costs, human resource readiness, and data security. AI integration has strong potential to increase banking operational efficiency and competitiveness. Effective implementation strategies and regulatory support are essential for optimal results.